Test-retest reliability and validity of Jump Pro smartphone application for jump performance assessment - Lo, M.-T.; Sun, P.-C.; Pagaduan, J. C.; Crowley-McHattan, Z. J.; Chen, Y.-S. (Measurement in Physical Education and Exercise Science, 2026)
This study investigated the test-retest reliability and validity of a novel smartphone application (app), Jump Pro, for assessing jump performance. Fifty healthy adults (25 males = 21.7 ± 2.6 yrs; 25 females = 22.8 ± 3.0 yrs) performed countermovement jump (CMJ), bilateral depth jump (BDJ), and single-legged DJ (SDJ) in two visits. Jump performance was assessed using a Jump Pro and a PASCO force plate. A customized single-beam sensor was paired to a smartphone app for data collection and reliability was established using the Intraclass correlation coefficient (ICC3,1). The validity was examined via Bland-Altman difference plots. Results revealed strong agreement between Jump Pro and the criterion. The Jump Pro demonstrated good to excellent test-retest reliability and was valid to portable force plates across all jump performances. In conclusion, the Jump Pro is a reliable and valid tool for assessing jump performance.